Triangular Theory Of Love Vs Conditional Integration Theory Of Love Untuk Penelitian Pemasaran - Galuh Mira Saktiana (Universitas PGRI Yogyakarta, 2022)
Marketing research adopts many theories derived from psychology. The theory that is widely used for marketing research on the construct of brand love is the Triangular Theory of Love, where this theory discusses interpersonal love in which there are three components, namely intimacy, passion and commitment. This paper provides evidence that the theory turns out to have weaknesses that can be answered by the Conditional Integration Theory of Love and is a complement to the previous one, where this theory says that customer love is influenced by the desire to integrate with an object and the reality of integration with the object. Some of the existing weaknesses can be improved by the Conditional Integration Theory of Love, including the intimacy component which is more suitable for two-way relationships, then the commitment component leads to normative moral obligations. The love that occurs between the consumer and the brand is a one-way love, not a two-way give-and-take relationship. Therefore, a more appropriate theory for marketing research, especially brand love is the Conditional Integration Theory of Love.